Exploring the relationship between the acoustic features of the Quranic recitations and the activity of alpha and theta brainwaves - Kannan, Mohammed Abdalla (2021)
Auditory stimulations are frequently used as a form of sound therapy to induce relaxation and has been studied extensively utilising electroencephalography (EEG) and magnetoencephalography (MEG) techniques. For Muslims, the rhythmic Quranic recitations are widely recognised for similar relaxation and calming effects. To date, most EEG studies have employed sensor-level analysis to investigate the effects of listening to Quranic recitations on human brainwaves’ activity. However, such research has not considered the prosodic features (melody and rhythm) from the numerous Quranic recitation tempos and the influence these may have on the underlying brainwaves activity, namely alpha (8-13Hz) and theta (4-7Hz) which represent the common brainwaves studied in relation to Quranic recitations. This present study seeks to explore the link between the acoustic features of Quranic recitations and the activity of alpha and theta brainwaves in comparison with non- Quranic auditory stimuli, using a simultaneous EEG and MEG recording techniques and employing source modelling methods. Thirty (n=30) healthy subjects aged 21-35 years old were recruited following an informed consent as dual faith groups (15 Muslim and 15 non-Muslim). Five auditory stimuli were presented for 3 minutes each using spontaneous recordings of 61-channels EEG and 306-sensor MEG, which included three tempos Quranic Recitations (slow, moderate, fast), Arabic news and Arabic poem. The melodic and rhythmic patterns (spectral flux and pitch contour) were extracted using Sonic Visualiser software. The raw data were pre-processed using Brainstorm software following analysis pipeline applied to the resting-state EEG recordings. The spontaneous EEG and MEG recordings were transformed to frequency domain and source models of alpha and theta brainwaves were extracted. Power spectra analysis was used to identify the changes in activity of alpha and theta brainwaves during listening to different auditory stimuli and to compare the EEG and MEG activity between Muslim and non-Muslim subjects. The acoustic analysis revealed that the slow and moderate tempos of Quranic recitations have a steady fluctuating spectral flux and high-pitched contour. In contrast, the Arabic news, Arabic poem, and fast tempo had quickly fluctuating spectral flux and low-pitch contour. These findings indicates that the slow and moderate tempos have regular rhythm and attractive melody compared to the other auditory stimuli. Meanwhile, source modelling of EEG and MEG showed that alpha brainwaves’ activity was increased in both groups when listening to all three Quranic recitations, whereas the activity of theta brainwaves was increased only in non-Muslims while listening to all three Quranic recitations. For the non-Muslim group but not in Muslims, there was significant difference between the experimental conditions in the relative power of theta brainwaves over left ventromedial prefrontal cortex (p=.008) and the relative power of alpha brainwaves over the left precuneus (p=.007). These observations demonstrate that Quranic recitations elicit a relaxing response in both Muslim and non-Muslim individuals. The findings provided in this study signify that the familiarity and the prosodic features (melody and rhythm) of Quranic recitations are major elements that influence the activity of alpha and theta brainwaves. However, this study is the first to give empirical proof indicating varying tempos of Quranic recitations can produce alpha and theta brainwave activity in non-Muslims. This finding also provides the evidencebased basis to uplift the potential of Quranic recitations as a form of sound therapy to promote a state of mental relaxation, irrespective of the listener’s religious belief or background.